The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1007/s10640-004-3332-z
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Hypothetical Bias in Stated Preference Valuation

Abstract: A meta-analysis of hypothetical bias in stated preference valuation" (2005 Abstract. Individuals are widely believed to overstate their economic valuation of a good by a factor of two or three. This paper reports the results of a meta-analysis of hypothetical bias in 28 stated preference valuation studies that report monetary willingness-to-pay and used the same mechanism for eliciting both hypothetical and actual values. The papers generated 83 observations with a median ratio of hypothetical to actual value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
264
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 828 publications
(290 citation statements)
references
References 23 publications
8
264
2
2
Order By: Relevance
“…In this vein, we identify some methodology effects/biases such as: elicitation format, sample size, cheap talk script, payment vehicle, picture presentation and questionnaire translation. Some various meta-analysis studies that have evaluated these biases and/or effects in primary valuations include scoping effects (Smith and Osborne 1996, Ojea and Loureiro 2011) to hypothetical biases (Murphy et al, 2005). Nevertheless, this study extends the previous works by identifying more forms of biases and/effects thereby examining how these affect benefit transfer values in other varied sites.…”
Section: Background To Coral Recreation Meta-analysismentioning
confidence: 70%
“…In this vein, we identify some methodology effects/biases such as: elicitation format, sample size, cheap talk script, payment vehicle, picture presentation and questionnaire translation. Some various meta-analysis studies that have evaluated these biases and/or effects in primary valuations include scoping effects (Smith and Osborne 1996, Ojea and Loureiro 2011) to hypothetical biases (Murphy et al, 2005). Nevertheless, this study extends the previous works by identifying more forms of biases and/effects thereby examining how these affect benefit transfer values in other varied sites.…”
Section: Background To Coral Recreation Meta-analysismentioning
confidence: 70%
“…They also reported that the effect of the hypothetical bias was considerably lower for private goods compared to public goods. By the same token, Murphy et al (2005) also carried out a meta-analysis of 28 studies and reinforced the findings of List and Gallet (2001) by showing that the mean ratio of the hypothetical to actual values is around 1.35 and that the bias increased when public goods were valued.…”
mentioning
confidence: 79%
“…The hypothetical bias, however, still represents a challenging issue for the CV. It is well known that the hypothetical bias occurs when the individuals overstate their willingness to pay (WTP) in the hypothetical settings due to, among others, the lack of economic incentive to reveal their true valuations (List and Gallet 2001;Murphy et al 2005). List and Gallet (2001) conducted a meta-analysis of 29 experimental studies which revealed that the subjects in average overstate their preferences by a factor of 3 in hypothetical settings.…”
mentioning
confidence: 99%
“…Approximately 62% also indicated that they believed that they were stating dives that they "think" they will take, rather than that they "hoped" they would take. Furthermore, the broad literature suggests that people tend to overstate their values in hypothetical settings (Little and Berrens 2004;Murphy, Stevens and Weatherhead 2005;Whitehead 2005). To examine the potential for the existence of "hypothetical bias", we asked three questions to examine respondents' perceived consequentialism of their survey responses.…”
Section: Survey Frameworkmentioning
confidence: 99%
“…Within the stated preference literature, research has shown that values for non-market goods derived from stated preference survey techniques often exceed those elicited using revealed preferences (List and Gallet 2001;Murphy et al 2005). Therefore, our model specification includes a dummy variable representing those observations elicited using our stated preference methodology.…”
Section: Conceptual Frameworkmentioning
confidence: 99%